Produktivitas Karya llmiah Dosen Sekolah Tinggi Agama Islam Negeri Malang: Analisis terhadap Jurnal Ilmiah el-Harakah 1997 - 2000 - Sulalah, Sulalah (ULUL ALBAB Jurnal Studi Islam, 2004)
By using case study in STAIN Malang, this study objected to obtain some data about the profile of and the motivations and obstacles of scientific productivity facing by lecturer in STAIN Malang. The study gives us informations that Muhaimin, M. Zainuddin, and Roibin are the most productives lecturer. Various spirits of life and of credibility and also the spirit of professionalism of lecturer represent big motivations in lecturer productivity, while, workload in family, administration and occupy most position in some communities often become resistors of lecturer productivity in STAIN Malang.